Marine diatom response to oceanographic and climatic changes in the NW South China Sea since the penultimate glacial interval. (December 2020) - Zhang, Jinpeng; Tomczak, Michał; Witkowski, Andrzej; Li, Chao; Chen, Chixin; McCartney, Kevin
Graphical abstract: Highlights: Detailed diatom analysis for regional oceanographic and climatic reconstruction in NW SCS. Six Local Diatom Assemblage Zones (LDAZ) responded to MIS 6-1 within glacial-postglacial cycle. The LDAZs have potential capability for regional biostratigraphy correlation in NW SCS. Diatom species distribution responded to quite rapid climate changes during MIS 4/3 transition. Abstract: The species abundances and assemblage of fossil diatoms are used as micropaleontological proxy to reconstruct the northwestern South China Sea continental margin paleo-environment over the last glacial - interglacial cycle and Holocene. Analysis of fossil diatom assemblages in piston core 111PC show a flora over the most recent ~160 kyr. BP dominated by tropical-subtropical planktonic and coastal species, assigned to six local diatom assemblage zones similar to foraminifera-based marine oxygen-isotope stages (MIS 6-1). Diatom abundance and species fluctuations in the core profile study area respond to the glacial – interglacial climate gyration and climate instability. Diatom abundance was higher in the late-Würm, compared to mid-Würm glacial and postglacial (Holocene) stages and even lower during the Riss and early-Würm glacial stages. Change tendency of diatom abundance is significantly different from stations to the southwest but comparable to northeast South China Sea. In MIS 5, relative abundance of tropical diatom taxa decreases upward in response to climate shifts from interglacial to last glacial interval. Diatom species distribution with higher relative abundance of coastal taxa responded to climate-fluctuation during the MIS 4 and MIS 3 transition while biased by local deposition character.